PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP HASIL BELAJAR GEOGRAFI MATERI ATMOSFER KELAS X IPS SMA PERTIWI 1 PADANG - Azra, Hasanatul; Rahmanelli, Rahmanelli (JURNAL BUANA, 2024)
This study aims to determine the effect of applying the Numbered Heads Together cooperative learning model to the learning outcomes of Atmospheric Geography material for class X IPS SMA Pertiwi 1 Padang. This type of research is a quantitative based on quasi-experimental design pretest-posttest. The population in the study was class X IPS SMA Pertiwi 1 Padang. Sampling was taken using purposive sampling technique, namely class X IPS 1 with a total of 35 people as the experimental class and class X IPS 2 with a total of 30 people as the control class. The research instrument was in the form of multiple choice test questions (pretest-posttest). Data collection techniques used tests, observations and documentation which were analyzed using the Normality test, Homogeneity test, Z test and Normalized Gain test. The average pretest for the experimental class was 44.57 while the control class was 45.07 with a difference of 0.50. The average posttest for the experimental class was 81.89 while for the control class it was 72.53 with a difference of 9.36 meaning that the learning outcomes of the experimental class were higher than the control class. The Z test shows Zcount≥Ztable=3.34≥1.96 then H0 is rejected, meaning that there is an influence of the application of the Numbered Heads Together cooperative learning model on learning outcomes. The normalized gain test for the experimental class is 0.71 with the criteria for a high increase, while the control class is 0.52 with the criteria for a moderate increase. Thus the learning outcomes using the Numbered Heads Together cooperative learning model are more effective than using the direct learning model. Keywords: Numbered Heads Together, Experiments, Geography Learning Outcomes